2003
DOI: 10.1590/s0101-81752003000200027
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a bat assemblage (Mammalia, Chiroptera) in Serra do Caraça Reserve, South-east Brazil

Abstract: ABSTRACT. The Serra do Caraça Reserve is situated in the southern portion of the Espinhaço Mountain Range, and contains areas of "campos de altitude", "cerrado" and atlantic forest. This study had as its objective the registering of the bats species that occur in the reserve. The data collection was carried out in one year through monthly samplings, using mist nets set on trails, and also through hand capture. A total of 246 individuals were collected (0.72 bats/net-hour), distributed across 15 species, belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0
18

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 8 publications
5
14
0
18
Order By: Relevance
“…Conforme a curva acumulativa de capturas feita para o presente estudo (Fig. 2), observa-se que é necessário um maior período de amostragem para que o número de espécies esteja bem representado, pois somente com a estabilização da curva em uma linha contínua, poder-se-á afirmar que a comunidade foi bem amostrada, como já demonstrado em diversos estudos com morcegos, feitos no Brasil e no exterior (BERNARD 2001b, AGUIRRE 2002, AGUIRRE et al 2003, FALCÃO et al 2003.…”
Section: Discussionunclassified
“…Conforme a curva acumulativa de capturas feita para o presente estudo (Fig. 2), observa-se que é necessário um maior período de amostragem para que o número de espécies esteja bem representado, pois somente com a estabilização da curva em uma linha contínua, poder-se-á afirmar que a comunidade foi bem amostrada, como já demonstrado em diversos estudos com morcegos, feitos no Brasil e no exterior (BERNARD 2001b, AGUIRRE 2002, AGUIRRE et al 2003, FALCÃO et al 2003.…”
Section: Discussionunclassified
“…Some studies have shown these bat assemblages in different areas: trophic relations in the Phyllostomidae from Panga Reserve, southeastern Brazil (Pedro and Taddei, 1997); bat community structure in a south-east Brazilian reserve in a transition zone between Cerrado and Atlantic Forest (Falcão et al, 2003); diversity of a Cerrado habitat in central Brazil (Zortéa and Alho, 2008). Recent literature has synthesised the number of species and distribution in Brazil (Reis et al, 2007), as well as a bat community in a savanna habitat in Bolivia, near the Pantanal Aguirre, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Information on the mammalian fauna of Caraça was additionally obtained from studies conducted at the site over the last decade (Falcão et al 2003;Talamoni 2003, 2004;Cordeiro-Júnior and Talamoni 2006;Talamoni and Assis 2009;Cordeiro-Júnior et al 2010), which are now presented in this work, and new study with the use of camera traps for medium and large mammals, and through interviews with residents and staff of the locality. Below are summarized the different methods employed in obtaining records of mammals.…”
Section: Data Collectionmentioning
confidence: 99%
“…Sampling of bats was performed by capturing individuals using mist-nets in different habitats of Caraça, which included areas of forest (Tabuões and Tanque Grande), cerrado (Cascatinha trail), and buildings within, and adjacent to, Sanctuary (Figure 1; details in Falcão et al 2003).…”
Section: Data Collectionmentioning
confidence: 99%